Gender-based analysis on self-efficacy beliefs of pre-service teachers and their readiness in taking licensure examination - Vilma Muega-Geronimo; Marites D. Carlos (International Journal of Evaluation and Research in Education (IJERE), 2023)
The study aimed to determine whether preservice teachers’ self-efficacy belief differs according to gender and whether this belief relates to their readiness in taking the licensure examination for teachers (LET). Participants of the study were 545 preservice teachers who were undergoing in-service training both from the secondary and elementary programs that came from four campuses of the university. The researcher utilized a descriptive quantitative approach with weighted mean, t-test for the independent sample, and Pearson R correlation statistical treatments for the data. Results revealed that females are statistically higher in self-efficacy beliefs than their male counterparts. Further, the study disclosed that female preservice teachers are significantly more ready to take the examination than their male peers. In addition, the male students’ self-efficacy beliefs statistically have a positive significant relationship to their readiness to take examination. Meanwhile, a positive significant relationship exists also between self-efficacy beliefs and readiness in taking the test with their female counterparts.